PELAYANAN AKADEMIK (STUDI KASUS PELAYANAN PORTAL AKADEMIK DI UNIVERSITAS RIAU) - Arjuni, Windra; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Today, in globalization era, service quality is one of important factors in service institution. Good service is a service that can give and adjust consumer needs and also give good value to the consumers. Riau University is one of public education institutions that give education services. Education service in university divide into two kinds, they are; teaching service and administration service. UPT TIK UR (Technical And Operational Units And Information Communication Technology Of Riau University) is one of units operational technical that is specifically as supporting teaching and learning process and also helping the implementation of university tridharma that give service to academician in using online medias they are; academic portal, this is one of facilities that can be used anytime and wherever that provide for students college. The objectives of the research were to find out the service quality and factors that influence of academic portal. This research used E-SERVQUAL theory ( Electronic Service Quality). This research used descriptive research with qualitative method based on the data that is taken in UPT TIK UR. In collecting the data the researcher used observation, interview, and library study and technique of snowball sampling. This research was conducted in UPT TIK ( Technical And Operational Units And Information Communication Technology Of Riau University) Riau University at H. R Soebrantas street simpang baru Pekanbaru city. After doing the research, the writer found that the service quality of academic portal was good. There were factors that influenced service of academic portal like system, network, inadequate capacity portal, lack of infrastructure, fund, nature ( rain, hurricane, thunderclap, and natural resources).Keywords : service quality, academic portal.